Social sustainable development green brand value in education impact strategic alliance investment decision evaluation - Ko, Chuan-Chuan; Liu, Chien-Yu; Liu, Chunmei (Frontiers in Energy Research, 2023)
Green brand is a consumer experience. Educational hospitality attaches importance to green brands, and consumers' preference for green brands has become the current business practice of environmental protection and sustainable development. Strategic alliances drive competitiveness and exert multiplier effects. Commodity diversification is an important key factor in enhancing competitiveness and sustainable development. This study uses the real options approach to construct a dynamic strategy model, which explains the optimal occupancy pricing threshold and optimal green brand value investment strategy threshold on different influence variables and evaluates the difference between hospitality alliances with green brand restaurant and hospitality providers that create their own brand specialty restaurants. This study provides corresponding strategies for the development of a larger consumer market and market share for hospitality and the feasibility of sustainable development. The results show that the threshold of hospitality alliances with green brand restaurant is lower and will gain higher returns. However, if the economy is booming, it is more advantageous for hospitality alliances to adopt their own innovative brand specialty restaurants. It is recommended that managers consider developing innovative catering services and quality when hospitality faces strong competition. The choice is to form an alliance with a green brand restaurant or create its own brand specialty restaurant to enhance hospitality's popularity to attract more customers. This will contribute to the sustainable development of hospitality. The results of the analysis provide a reference for managers to make appropriate investment decisions for restaurant management at an appropriate time.